A resposta de João Daniel ao projeto português para o Amazonas - Tamura, Anderson Tsuioshi Alves (2010)
This paper aims to analyse jesuit priest João Daniel s work, that started his path as a representaive to the Inacian Order in the portuguese colons to the north in the state of Grão Pará e Maranhão during the secound half of the XVIII century, a period when the conflict between the inacians and the portuguese government were constant. That was the context where were the historic figuring of priest João Daniel in the midle of the dispute between the crown and the jesuitical Order, writing hes works. João Daniel propose a economic projet for the Amazon based upon the jesuits knowledge about the fauna, flora and geography of the region which he considered the true Amazon treasures. At the same time, he debated and answered the Portuguese State s accusations against the order and carried through discussion about the nature and fauna in the New Word. That is the perspective througt which we propose own study, analyzing this Inacian´s Work, praising his work as an important voice in the XVIII century, bearing in the mind that that his work approaches a number of relevant questions such as the importance of the fauna and flora, the need for adapting the environment toward, economic development and the indigenous handwork functionality